Sovereignty, Territory and the International Lawyer's Dilemma - Greig, Donald W. (Osgoode Hall Law Journal, 1988)
A historical perspective of the rules of territorial acquisition and of Antarctic sovereignty provides a basis for an examination of the conflict between international law and state sovereignty. While there may not be any immediate redress against the unlawful action of powerful states, the evolution of international law provides a value system and rule-making capacity which does not grant legitimacy to such actions.